Response of aphid predators to synthetic herbivore induced plant volatiles in an apple orchard - Gencer, Nimet Sema; Kumral, Nabi Alper; Altin, Irem; Pehlevan, Bilgi (Revista Colombiana de Entomología, 2019)
The indirect defence compounds termed herbivore induced plant volatiles (HIPVs), which are used to attract beneficial fauna, are one of the most effective biological control tools for the aggregation of natural enemies of key pests. The aim of this study was to test the attraction of three aphid predators of the Chrysopidae, Coccinellidae and Syrphidae families using synthetic formulations of four main HIPVs [methyl salicylate (MeSa), benzaldehyde (B), linalool (L) and farnesene (F)] alone and in binary combinations (MeSa + B; MeSa + F; MeSa + L; F + B; B + L; F + L) in an apple orchard in the Bursa province of Turkey. This study was the first demonstration of the attraction of these aphid predators to single and binary combinations of synthetic HIPVs in an apple orchard. A larger number of coccinellids were captured using single treatments of both B and F than with other HIPV combinations. Furthermore, the chrysopid individuals studied were significantly attracted to traps baited with single HIPVs. In addition, the binary combination of MeSa + L significantly attracted more Syrphids than in both single treatments and control traps. Thus, some of the HIPV’s tested were found to have potential value for the congregation of aphid predators in apple orchards.